Ergothioneine Improves Aerobic Performance Without Any Negative Effect on Early Muscle Recovery Signaling in Response to Acute Exercise - Fovet, Théo; Guilhot, Corentin; Delobel, Pierre; Chopard, Angèle; Py, Guillaume; Brioche, Thomas (Frontiers in Physiology, 2022)
Physical activity is now recognized as an essential element of healthy lifestyles. However, intensive and repeated exercise practice produces a high level of stress that must be managed, particularly oxidative damage and inflammation. Many studies investigated the effect of antioxidants, but reported only few positive effects, or even muscle recovery impairment. Secondary antioxidants are frequently highlighted as a way to optimize these interactions. Ergothioneine is a potential nutritional supplement and a secondary antioxidant that activates the cellular NRF2 pathway, leading to antioxidant response gene activation. Here, we hypothesized that ergothioneine could improve performance during aerobic exercise up to exhaustion and reduce exercise-related stress without impairing early muscle recovery signaling. To test this hypothesis, 5-month-old C56B6J female mice were divided in two groups matched for maximal aerobic speed (MAS): control group (Ctrl; n=9) and group supplemented with 70mg ergothioneine/kg/day (ET; n=9). After 1 week of supplementation (or not), mice performed a maximum time-to-exhaustion test by running on a treadmill at 70% of their MAS, and gastrocnemius and soleus muscles were collected two hours after exercise. Time to exhaustion was longer in the ET than Ctrl group (+41.22%, p<0.01). Two hours after exercise, the ET group showed higher activation of protein synthesis and satellite cells, despite their longer effort. Conversely, expression in muscles of metabolic stress and inflammation markers was decreased, as well as oxidative damage markers in the ET group. Moreover, ergothioneine did not seem to impair mitochondrial recovery. These results suggest an important effect of ergothioneine on time-to-exhaustion performance and improved muscle recovery after exercise.